THE FRANK-HERTZ EXPERIMENT. EINSTEIN THEORY - Taylanov, Nizom; Urazov, Abdixoliq; Khamdamov, Begali (Физико-технологического образование, 2022)
In this article we investigate the problem of modeling laboratory work in quantum physics under the name "Study of the photoelectric effect." The dependence of the light intensity and frequency on the anode voltage is investigated. There is a known voltage value between the anode and the photocathode, where the photocurrent is zero. The process of formation of the photoelectric effect at a given voltage as a result of a change in the parameter U was analyzed from the point of view of modeling